Aṭṭhāsila: Embracing Buddhist Virtues at Gentha Dharma Prabhassa Monastery for Holistic Benefits - Widhiastuti Widhiastuti; Santacari Santacari (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP) Sekolah Tinggi Ilmu Agama Buddha Smaratungga, 2023)
The practice of Aṭṭhāsila holds significant importance for Buddhists at the Gentha Dharma Prabhassa monastery, becoming an eagerly awaited annual program before the Tri-Holy Vesak Day. This study aims to delve into Buddhist perspectives on Aṭṭhāsila, its implementation, and the benefits it offers. Employing a qualitative descriptive method with an ethnographic approach, the research showcases the profound enthusiasm of Buddhists at the monastery towards the Aṭṭhāsila program. The findings demonstrate that the practice of Aṭṭhāsila not only enriches the individual lives of practitioners but also exerts positive influences on the economic well-being of their households (gharavasa). This study sheds light on the holistic impact of Aṭṭhāsila, revealing its significance in fostering a meaningful and virtuous life within the Buddhist community at the Gentha Dharma Prabhassa monastery. this study adds valuable knowledge to the field of religious studies, shedding light on the significance of Aṭṭhāsila in fostering spiritual growth, social harmony, and economic well-being within the context of the Buddhist community.